Treatment of lateral epicondylitis using skin-derived tenocyte-like cells. Issue 4 (17th February 2009) - Connell, D; Datir, A; Alyas, F; Curtis, M
Abstract : Objectives: To culture collagen-producing cells derived from skin fibroblasts and o evaluate prospectively the safety and potential use of this cell preparation for treatment of refractory lateral epicondylitis in a pilot study. Design: Prospective clinical pilot study. Setting: Institution-based clinical research. Patients: A total of 12 patients (5 men and 7 women; mean age 39.1 years) with clinical diagnosis of refractory lateral epicondylitis. Interventions: Laboratory-prepared collagen-producing cells derived from dermal fibroblasts were injected into the sites of intrasubstance tears and fibrillar discontinuity of the common extensor origin under ultrasonography guidance. Main outcome measures: The outcome assessment was performed over 6 months. The Patient-Rated Tennis Elbow Evaluation (PRTEE) scale was used to assess pain severity and functional disability. Tendon healing response was measured using four criteria on ultrasonography: tendon thickness, hypoechogenicity, intrasubstance tears and neovascularity. Results: Cell cultures rich in collagen-producing cells was successfully prepared. After injection, the median PRTEE score decreased from 78 before the procedure to 47 at 6 weeks, 35 at 3 months and 12 at 6 months after the procedure (p<0.05). The healing response on ultrasonography showed median decrease in: (1) number of tears, from 5 to 2; (2) number of new vessels, from 3 to 1; and (3) tendon thickness, from 4.35 to 4.2 (p<0.05). Of the 12 patients, 11 had a satisfactory outcome, and only one patient proceeded to surgery after failure of treatment at the end of 3 months. Conclusions: Skin-derived tenocyte-like cells can be cultured in the laboratory to yield a rich preparation of collagen-producing cells. Our pilot study suggests that these collagen-producing cells can be injected safely into patients and may have therapeutic value in patients with refractory lateral epicondylitis.